5G Technology: Towards Dynamic Spectrum Sharing Using Cognitive Radio Networks - Ahmad W.S.H.M.W.; Radzi N.A.M.; Samidi F.S.; Ismail A.; Abdullah F.; Jamaludin M.Z.; Zakaria M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cognitive radio; Network architecture; Surveys; Cognitive radio network; Cognitive radio technologies; Dynamic spectrum sharing; Efficient managements; Enabling technologies; Issues and challenges; Spectrum efficiency; Spectrum sharing; 5G mobile communication systems